Private sector involvement and Public Private Partnership (PPP) in Malaysia - Ismail, Suhaiza; Asuhaimi, Fadhilah (IIUM Press, 2013)
This chapter describes the development of private sector involvement in undertaking public sector projects in Malaysia. The initiative for involvement of private sector started with the privatization policy introduced in 1983 under the mid-term review of the Fourth Malaysian Plan (1981-1985). Due to the success of the privatization policy and the aim of the government to further encourage private sector involvement in delivering public sector infrastructure and services, Public Private Partnership (PPP) was introduced in the Ninth Malaysia Plan (2006-2010). PPP was further emphasized in the recent Tenth Malaysia Plan (2011-2015).